Non-EU labor migration in Spain: exploring profiles and career paths - Anguiano Téllez, María Eugenia (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
This article examines the factors associated with the human capital and the social capital that favor or limit the incorporation of immigrants into the spanish labor market, exploring the demographic characteristics, family networks and the labor trajectories of three latin american, two african and one asian groups. the article is based on information gathered in a survey conducted by the instituto universitario de estudios sobre migraciones in 1998. the sample using quotas considered the concentration patterns of immigrants in spain. the incorporation of immigrants in few economic sectors suggests the existence of labor replacement in jobs that natives have left or the construction of labor niches. one option does not exclude the other.